Pengolahan Air Gambut Dengan Teknologi Biosand Filter Dual Media - Usman, Ratika; Darmayanti, Lita; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Clean water fulfillment become a common problem and yet to be solved  especially for isolated countryside area. Clean water can be defined as daily needs water and its quality should fulfill the requirement of healthy water based on laws and can be drinked when it is cooked.  High demand of clean water for peat area community  made this research to be important.   The utilization of simple water treatment system is expected to solve the problem of clean water for the comunity. Treatment method used in this research is biosand filter with dual media of pumice and quartz sand. Water quality parameter tested are pH, color, solution degree, and organic contain (KmnO4). Statistical analysis used in this research is two ways varian analysis (Anova). The result of the research shows that the best arrangement of filtering media layers are pumice at the top and quartz sand underneath it and for the thickness of the filtering media, the best thickness to used is 40 cm of pumice thickness and 20 cm of quartz sand thickness. Dual media biosand filter can generate maximum efficiency in raising pH value of 36,54%, lowering peat water solution level of 88,41 %, lowering peat water color value of 92 ,33 % and also lowering organic content of 93,24 %. Keywords : dual media biosand, peat water, pumice , sand.